2011
DOI: 10.1186/1475-2840-10-62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silibinin on endothelial dysfunction and ADMA levels in obese diabetic mice

Abstract: BackgroundCardiovascular diseases (CVD) in diabetic patients have endothelial dysfunction as a key pathogenetic event. Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase (NOS), plays a pivotal role in endothelial dysfunction. Different natural polyphenols have been shown to preserve endothelial function and prevent CVD. In this study, we assessed the effect of silibinin, a widely used flavonolignan from milk thistle, on ADMA levels and endothelial dysfunction in db/db mice.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…Indeed, liver JNK phosphorylation was reduced to control levels in treated animals [57]. In obese diabetic mice, silybin administration markedly decreased plasma levels of asymmetric dimethylarginine, an endogenous inhibitor of nitric oxide synthase that, as known, plays a pivotal role in endothelial dysfunction [58]. Finally, the antiviral action of silybin against HCV replication is also related to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, liver JNK phosphorylation was reduced to control levels in treated animals [57]. In obese diabetic mice, silybin administration markedly decreased plasma levels of asymmetric dimethylarginine, an endogenous inhibitor of nitric oxide synthase that, as known, plays a pivotal role in endothelial dysfunction [58]. Finally, the antiviral action of silybin against HCV replication is also related to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 93%
“…Silibin decreases ADMA levels in db/db mice to a level that is lower than in their heterozygous lean counterparts (db/m), which served as controls [17]. In experimentally induced diabetic retinopathy, silibin seems to have a favorable effect as vascular leukostasis and levels of retinal ICAM-1 are significantly reduced [18].…”
Section: Animal In Vivo Studiesmentioning
confidence: 99%
“…Potent scavenging properties have been demonstrated in hepatic and non-hepatic cells; 11,12 several in vivo studies showed that silibinin may exert beneficial effects in different types of liver injury 13,14 and in diabetes and its complications. 15 Previous clinical findings evidenced the efficacy of silibinin on insulin resistance and liver injury, assessed by surrogate markers, in patients with NASH; 16 the improvement of liver histology after silibinin treatment was recently reported in a multicenter randomized controlled trial. 17 However, the molecular mechanisms associated with the hepatoprotective activity of silibinin in NASH remain to be elucidated.…”
mentioning
confidence: 99%